(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Internet of Things (IoT) is revolutionizing the way physical devices interact by integrating sensors and computational capabilities, enabling seamless communication and remote access to services. Initially developed to connect devices for enhanced